PEMBELAJARAN KARAKTER BERBASIS NILAI-NILAI PESATREN (Studi atas Pondok Pesantren Al-Isâaf Kalabaan, Guluk-guluk Sumenep) - Solichin, Mohammad Muchlis (STAIN PAMEKASAN, 2017)
Pesantren as a traditional islamic education institution runs the education system supported by values as the studentsâ characters. Keeping values of pesantren exists through teaching learning can strenghthen the taughness of the pesantren in keeping its existence in the society. This research is trying to analyze the pesantrenâs values which become the characteristics of the santri and this values is developed in the teaching learning process. This research uses qualitative research with observation, interview, and documentation as the data collection procedure. From the result of the research, it can be seen that the santriâs characteristic valuesÂ which are defended in the education process in al-Is.âaf Islamic boarding school are sincerity,survavibility, simplicity, asketism, spirit to teach and do worship to ALLAH.